2009
DOI: 10.3168/jds.2008-1255
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of lactoferrin content in bovine milk

Abstract: Bovine lactoferrin (LF) is mainly present in milk and shows important physiological and biological functions. The aim of this study was to estimate the heritability and correlation values of LF content in bovine milk with different economic traits as milk yield (MY), fat and protein percentages, and somatic cell score (SCS). Variance components of the studied traits were estimated by REML using a multiple-trait mixed model. The obtained heritability (0.22) for LF content predicted using mid-infrared spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 24 publications
7
16
2
5
Order By: Relevance
“…This observation confirms the previous conclusions of many reports showing the increase in lactoferrin content in milk from infected udders compared with healthy cows (Kawai et al 1999, Hagiwara et al 2003, Cheng et al 2008b, Arnould et al 2009). LTF level in milk is believed to be a good indicator of mastitis because of a high positive correlation between LTF and SCC (Lindmark-Mansson 2006, Soyeurt et al 2007, Arnould et al 2009) and is also useful in detecting the false-positive results of screening tests for antibiotic residues in milk (Malinowski et al 2008). Cheng et al (2008b) observed a significant positive correlation of lactoferrin concentrations between serum and milk in early phase of the immune response.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This observation confirms the previous conclusions of many reports showing the increase in lactoferrin content in milk from infected udders compared with healthy cows (Kawai et al 1999, Hagiwara et al 2003, Cheng et al 2008b, Arnould et al 2009). LTF level in milk is believed to be a good indicator of mastitis because of a high positive correlation between LTF and SCC (Lindmark-Mansson 2006, Soyeurt et al 2007, Arnould et al 2009) and is also useful in detecting the false-positive results of screening tests for antibiotic residues in milk (Malinowski et al 2008). Cheng et al (2008b) observed a significant positive correlation of lactoferrin concentrations between serum and milk in early phase of the immune response.…”
Section: Discussionsupporting
confidence: 82%
“…The low LTF concentration during the first 2 months of lactation and the highest during the last 3 months could be explained by the dilution effect observed by Arnould et al (2009) and Soyeurt et al (2007) who obtained a negative genetic correlation between daily milk production and LTF content of -0.25 and -0.36, respectively. A significant increase in LTF concentration in the following stages of lactation was in agreement with the results obtained by other authors (Hagiwara et al 2003, Cheng et al 2008a.…”
Section: Discussionmentioning
confidence: 99%
“…Beberapa laporan menyebutkan aktivitas antibakterial laktoferin baik pada penelitian in vitro maupun in vivo (Arnould et al, 2009;Nibbering et al, 2001;Pawlik et al, 2009, Wakabayashi et al, 2006. Laktoferin menyebabkan membran bakteri gram negatif tidak stabil karena terjadi pemblokiran interaksi antara LPS dengan LPS signaling (CD 14) (Rainard and Riollet, 2006).…”
Section: Pendahuluanunclassified
“…Isolasi DNA dari sampel darah dilakukan dengan menggunakan metode ekstraksi phenol-chloroform (Sambrook et al 1989) yang telah dimodifikasi untuk sampel darah yang disimpan dalam alkohol. Isolasi DNA dari sampel susu dilakukan dengan menggunakan metode ekstraksi DNA dari sel somatik (Arnould et al, 2009 …”
Section: Ekstraksi Dna Dan Pcrunclassified
See 1 more Smart Citation